Leadership Training Toolkit for State-Owned Enterprises : Boards and Owners - World Bank Group (World Bank and International Finance Corporation, Washington, DC, 2021)
The Leadership Training Toolkit for State-Owned Enterprises (‘SOE Leadership Toolkit’) was developed jointly by the World Bank and IFC (World Bank Group) to support countries’ efforts to build capacity of SOE boards and senior managers. It also endeavors to strengthen state ownership and oversight institutions, given the growing role and impact of SOEs on public finances, the economy, and delivery of services. The SOE Leadership Toolkit addresses the growing need for curriculum content and teaching methodologies specifically adapted for SOEs. And it allows for use by different training providers, such as government training institutions, Institutes of Directors, corporate governance associations, and professional bodies or universities. The SOE Leadership Toolkit is designed for experiential learning by executives and officials and can meet a variety of training needs and priorities of a range of sponsoring organizations. Its flexible and modular approach can be readily customized to fit different country contexts and training needs. Its 15 modules cover 1) fundamentals of corporate governance (and the role of the state); 2) the board, 3) strategy, risk, and performance, and 4) control environment, transparency, and disclosure. Cross-cutting these modules are four themes: 1) gender and diversity, 2) climate risk and resilience, 3) Maximizing Finance for Development, and 4) corruption and integrity.